Motivation of "Trust" in Education of Children Categories Asperger Disorder (AD) - Saidina Usman; Ridwan Ridwan; Siti Marwah; Nori Nopita Sari (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
Every child is unique and trustworthy from God, including children in the category of Asperger Disorder (AD). This study aims to analyze the experience of being a parent in educating “children” in the AD category. Islam teaches the concept of mandate as a parent. As a “knife of analysis”, T. Parson’s theory is used in observing the efforts of parents to realize a harmonious family in a “trustful” frame. Obtaining data is done by using interview and observation techniques. The results showed that by considering children as “God’s mandate”, can raise awareness of educating and caring for children according to their needs. This is driven by factors of knowledge, appreciation, and religious practice of the child’s parents.